Sequential optimization, front-loaded information, and U.S. consumption - Alpo Willman (European Central Bank (ECB), 2007)
In an overlapping generations maximization framework with consumers, whose information on uncertain future income realizations is front loaded, a closed form aggregate consumption function with CRRA preferences is derived. To have a closed form solution we assume that consumers solve their intertemporal optimization problem sequentially. First they assess riskadjusted life-time wealth and then the optimal consumption path. The derived model captures precautionary saving, which is dependent on the human to non-human wealth ratio. On aggregate level, after accounting for habit formation, the model is able to explain both the short-run (e.g. the excess sensitivity and the excess smoothness puzzle) and long-run stylized facts of the U.S. consumption data.
Keywords: D11; D12; D82; E21; 330; Consumption; habit persistence; Information; Precautionary Saving; Konsumtheorie; Overlapping Generations; Sparen; Asymmetrische Information; Risikoaversion; Theorie; USA